2017
DOI: 10.3390/su9122330
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Particulate Pollution (PM2.5 and PM10) and Their Spacescale-Dependent Relationships with Meteorological Elements in China

Abstract: Particulate matter (PM) pollution in China has an obvious characteristic of spatial distribution. It is well known that intensive anthropogenic activities, such as fossil fuel combustion and biomass burning, have great influence on the spatial distribution of PM pollution. However, the spacescale-dependent relationships between PM concentrations and weather conditions remain unclear. Here, we investigated the characteristics of two types of particulate pollution, including PM 2.5 and PM 10 , and their spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The ratio between PM 10 and PM 2.5 was generally constant and was equal about 1.1, and the ratio between PM 2.5 and PM 1 was at the level of 1.5. Such simple relationships might be not adequate for ambient air monitoring, where PM mass ratios depend on the pollutant sources and may change during the year [47,48].…”
Section: Measurements Resultsmentioning
confidence: 99%
“…The ratio between PM 10 and PM 2.5 was generally constant and was equal about 1.1, and the ratio between PM 2.5 and PM 1 was at the level of 1.5. Such simple relationships might be not adequate for ambient air monitoring, where PM mass ratios depend on the pollutant sources and may change during the year [47,48].…”
Section: Measurements Resultsmentioning
confidence: 99%
“…In the next line, we update the value of PM_Image by multiplying the division result with 55.40. This 55.40 refers to the average PM 2.5 concentration of 55.40 µg/m 3 if the relative humidity of the air is above 87% [46]. 2).…”
Section: Neural Network Representationmentioning
confidence: 99%
“…The IPCC report [2] shows that an increase in the frequency of extreme rainfall is likely to occur in most areas during the 21st century with different emissions scenarios. Recent studies by [3,4] reported that human activities played a leading role in increasing climate change impacts. The projected results of these changes include flooding, damage to crops, soil erosion, adverse effects on surface and groundwater quality, water scarcity, water contamination, disease outbreak, loss of properties, disruption of the settlement, and other socio-economic challenges [5].…”
Section: Introductionmentioning
confidence: 99%